Proceedings of the 15th ACM International Conference on Computing Frontiers 2018
DOI: 10.1145/3203217.3203278
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability analysis of Android auto infotainment apps

Abstract: With over 2 billion active mobile users and a large array of features, Android is the most popular operating system for mobile devices. Android Auto allows such devices to connect with an in-car compatible infotainment system, and it became a popular choice as well. However, as the trend for connecting car dashboard to the Internet or other devices grows, so does the potential for security threats. In this paper, a set of potential security threats are identified, and a static analyzer for the Android Auto inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Nevertheless, while in this ecosystem, connected car apps are a popular subject, little research has been conducted so far towards evaluating them under the security and privacy prisms. Mandal et al [9] presented a static analysis approach to discover software vulnerabilities in Android auto infotainment apps [10]. They examined more than 20 infotainment apps available in Google Play at that time, and concluded that nearly 80% of them were potentially vulnerable.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, while in this ecosystem, connected car apps are a popular subject, little research has been conducted so far towards evaluating them under the security and privacy prisms. Mandal et al [9] presented a static analysis approach to discover software vulnerabilities in Android auto infotainment apps [10]. They examined more than 20 infotainment apps available in Google Play at that time, and concluded that nearly 80% of them were potentially vulnerable.…”
Section: Related Workmentioning
confidence: 99%
“…This approach has been widely applied to the detection of SQL injections in Web applications [66], leakages of sensitive data [26,27], etc. A first attempt to apply such approach to a scenario similar to IoT was performed by Mandal et al [47] and Panarotto et al [58], that utilized this approach to detect leakages and injection vulnerabilities in Android automotive apps [49]. Huuck [40] discussed the use static code analysis to detect some of these types of issues.…”
Section: Related Workmentioning
confidence: 99%
“…Abstract Interpretation [13] is a mathematical framework, originally introduced by Cousot and Cousot in 1977, which provides a sound approximation of programs concrete semantics enabling sound answers to questions about programs run-time behaviors. The framework has been applied to different applications areas, from Security (e.g., [30,31]) to Databases (e.g., [32,33]), and to different programming environments (e.g., [34][35][36]). The idea is to lift concrete semantics to an abstract setting by replacing concrete values by suitable properties of interest, and simulating the concrete operations by sound abstract operations.…”
Section: Preliminaries: Abstract Interpretationmentioning
confidence: 99%